Crafting Unique Staycation Lodging Packages: Insights from Millennial Lifestyle Segmentation - Astuti, Sherly; Atrisia, Marchela Indah (Universitas Airlangga, 2024)
Background: In the post-pandemic landscape, the Tourism and Hospitality Industry, once a cornerstone of the Indonesian economy, experienced a significant downturn. This decline spurred the popularity of